QUALITY SCHEDULING INDEX WITHIN PRODUCT’S LIFECYCLE AND THE MONDERN SOCIETY - George Cristian GRUIA (Challenges of the Knowledge Society, 2018)
The purpose of this article is to provide a starting point for application of Quality Scheduling Index within the production process with an emphasis on the product lifecycle and a comparison with our society where due to demand there is an offer which should be in time, at the required level of quality and at the corresponding place of selling. The scope of the article is the expansion of the application of newly developed Quality Scheduling Index within several other branches of industry and an initial evaluation of its implementation. The article presents outputs of the author’s yet not published research and work in the filed of management and economics of the industrial enterprise and wants to become a starting point of the implementation of Quality Schedulin Index in enterprises which want to innovate their production process and reduce costs and dead time of the products / services within their lifecycle.